1974
DOI: 10.1017/s0007485300035847
|View full text |Cite
|
Sign up to set email alerts
|

Male accessory secretions, their use and replenishment in Glossina (Diptera, Glossinidae)

Abstract: The male accessory glands of Glossina austeni Newst. contain an apical secretion-a dense, opaque, whitish secretion at the apical end of the gland, and a diffuse secretion-a bulkier, more mobile, translucent, whitish secretion occupying nearly all the remainder of the gland. There is also a plug of clear solidified accessory material preventing the outflow of secretions from the resting gland. By immersing the whole accessory gland in a saline medium at pH 2-2, and then transferring the specimen to distilled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
1

Year Published

1976
1976
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 4 publications
0
18
0
1
Order By: Relevance
“…There was much individual variation in the development of apical bodies and it would be difficult to use apical body widths as a measure of male maturity. In G. m. morsitans , accessory gland secretions have been implicated in protecting sperm (P OLLOCK , 1974) and if re‐mating is truly rare in G. pallidipes (L EEGWATER VAN DER L INDEN and T IGGELMAN , 1984) then the accessory fluid may play a role in modifying female behaviour. The true role of accessory gland secretions in tsetse still needs to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was much individual variation in the development of apical bodies and it would be difficult to use apical body widths as a measure of male maturity. In G. m. morsitans , accessory gland secretions have been implicated in protecting sperm (P OLLOCK , 1974) and if re‐mating is truly rare in G. pallidipes (L EEGWATER VAN DER L INDEN and T IGGELMAN , 1984) then the accessory fluid may play a role in modifying female behaviour. The true role of accessory gland secretions in tsetse still needs to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the spermatophore formation in females and the changes in the accessory glands of males (apical body) after mating, suggested that the spermatophore precursor secretions are derived from male accessory glands (P OLLOCK , 1970). These observations suggested that measurements of the apical body width may be used to indicate the mating frequency of the males in the field (P OLLOCK , 1974), a phenomenon that could be important in monitoring mating in released sterile males.…”
Section: Introductionmentioning
confidence: 99%
“…Late in the copulation period the sperm migrate from the spermatophore to the spermathecae [17]. Accessory gland diameter in G. morsitans males increases only after feeding, and this increase appears to be due to accumulation of accessory gland fluid [13]. The influence of blood meals and neurosecretion on the synthesis of accessory gland secretions in tsetse flies has been demonstrated [14], and a positive correlation between spermatophore formation and insemination in G. morsitans has also been shown [17], thus insemination can only occur with the agency of the spermatophore.…”
mentioning
confidence: 99%
“…We have shown that the duration of copulation does not affect refractory behaviour once mating is between a sexually mature male and female. It has been shown that the development of the male accessory gland is dependent on the age of the fly (Pollock, 1974;Foster, 1976;Samaranayaka-Ramasamy, 1981). It has been shown that the development of the male accessory gland is dependent on the age of the fly (Pollock, 1974;Foster, 1976;Samaranayaka-Ramasamy, 1981).…”
Section: Discussionmentioning
confidence: 99%